Secret Messages : Codebreaking and American Diplomacy, 1930-1945 - Alvarez, David J. (Book collections on Project MUSE., 2000)
"In Secret Messages, David Alvarez provides the first comprehensive analysis of the impact of decoded radio messages (signals intelligence) upon American foreign policy and strategy from 1930 to 1945. He presents the most complete account to date of the U.S. Army's top-secret Signal Intelligence Service (SIS): its creation, struggles, and rapid wartime growth, and its contributions to the war effort."--Jacket.